2015
DOI: 10.3892/ol.2015.3148
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, complications and management of chronic neutrophilic leukaemia: A case report

Abstract: Abstract. Chronic neutrophilic leukemia (CNL) is a rare myeloproliferative neoplasm characterized by sustained neutrophilia and the absence of the Philadelphia chromosome or the BCR-ABL1 fusion gene. The present study reports the case of a 59-year-old Caucasian female that was referred to The Francisco Gentil Portuguese Institute of Oncology (Porto, Portugal) with constitutional symptoms (mainly asthenia), marked leukocytosis (51.33x10 9 /l with 90% neutrophils), macrocytic anemia and splenomegaly. Bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Paradoxically other studies have shown attenuated intracellular bactericidal activity in CNL 25 , 30 . Whether this biological phenomenon translates clinically to an increased propensity for infection in CNL patients is not clear 31 , 32 .…”
Section: Neutrophil Morphologymentioning
confidence: 99%
“…Paradoxically other studies have shown attenuated intracellular bactericidal activity in CNL 25 , 30 . Whether this biological phenomenon translates clinically to an increased propensity for infection in CNL patients is not clear 31 , 32 .…”
Section: Neutrophil Morphologymentioning
confidence: 99%
“…Neutrophil toxic granulations and Dohle bodies, though non‐specific and more frequently observed in neutrophilic leukemoid reactions, are not uncommon findings in CNL, and may suggest an activated neutrophil state . Reports pertaining to neutrophil function are inconsistent with some demonstrating increased vs attenuated bactericidal activity, and an unclear association with propensity to infection …”
Section: Disease Features and Diagnosismentioning
confidence: 88%
“…Lymphadenopathy and hepatomegaly are not common[ 12 ]. Hepatosplenomegaly, one of the main features of CNL, is a key indicator to distinguish leukemoid reaction from CNL[ 13 , 14 ]. Most patients with CNL have hepatosplenomegaly at the time of diagnosis, but hepatosplenomegaly is not common in the pathological manifestations of leukemoid reaction.…”
Section: Discussionmentioning
confidence: 99%